POSSIBILITY FOR EFFECTIVE PROTECTION AGAINST BIOLOGICAL WEAPONS (Annual of the Faculty of Philosophy in Skopje, 2019)
Although of micrometric magnitude, the biological weapon used as an act ofbioterrorism is a global danger. The possibility of using biological weapons, moreand more as a security measure, is considered as a means of subversive activity ratherthan a means of open warfare. Contemporary bacteriology provides a higher levelof techniques for creation of new deadly biological warfare agents. Internationalbans on the production and use of bio agents are not sufficient guarantee and protectionagainst the possible use of such agents in a future total war, nor are any obstaclefor use in terrorist goals. Here, the question arises about the possibilities for achievementof total protection expressed through the forms of bio-defence and biosafety.In this paper, there is a systematic attempt made to examine the (un)reasonablenessof the horrifying fear of modern genetic engineering technologies and the possibilitiesfor production of new, more dangerous agents. The results of this paper point torelatively reassuring /complacent view in the biomedical community for the premature,but still realistic possibility of an apocalyptic scenario as a consequence of theuse of bio agents. In addition to such views, scientific data on the relative efficacy ofexisting procedures for detection of agents and care of endangered/infected subjectson which antibiotic treatment, antibiotic-based therapies based on passive antibodiesand prophylaxis measures will be used are also discussed.
Keywords: BIOLOGICAL WEAPONS; BIOPROTECTION; VIRALITY; PROFILACY; IMMUNIZATION